Slum regeneration and sustainability: Applying the Extended Metabolism Model and the SDGs - Teferi, Z.; Newman, Peter (M D P I AG, 2017)
This paper examines the extent to which slum redevelopments have been successful in improving the sustainability of human settlements. Sustainability is measured in two ways: through the Extended Metabolism Model that looks at resource consumption, wastes, and liveability outcomes; and, through the framework of the Sustainable Development Goals (SDGs). The study compares the sustainability of informal slum settlements in Addis Ababa with high-rise slum clearance apartments; such clearance is the model mostly used for the world's informal settlements. The results show very little difference in resource consumption and waste produced but show liveability outcomes are mixed: Economic benefit is substantially improved in the high-rise areas due to becoming part of the formal economy, but community networks and trust are substantially lost when people transfer from the slums. This paper suggests that slum policy could be shifted from the Modernist high-rise slum clearance approach to a more organic, community-based renewal of the slums themselves in which infrastructure for energy, water, and waste can be brought in. New technology that fits into community-based governance structures allows such infrastructure to be a viable option, as well as enabling formal economic benefits. Some hybrid approaches may be needed in many slum improvement programs.